P14.32 Spatial discrepancies between FET PET and conventional MRI in patients with newly diagnosed glioblastoma. (6th September 2019) - Lohmann, P; Stavrinou, P; Lipke, K; Bauer, E K; Ceccon, G; Werner, J; Fink, G R; Shah, N J; Langen, K; Galldiks, N
Abstract: BACKGROUND: In patients with glioblastoma, the tissue showing contrast enhancement (CE) in MRI is usually the target for resection or radiotherapy. However, the solid tumor mass typically extends beyond the area of CE. Amino acid PET can detect tumor parts that show no CE. We systematically investigated tumor volumes delineated by amino acid PET and MRI in newly diagnosed, untreated glioblastoma patients. MATERIAL AND METHODS: Preoperatively, 50 patients with subsequently neuropathologically confirmed glioblastoma underwent O-(2-[ 18 F]-fluoroethyl)-L-tyrosine (FET) PET, fluid-attenuated inversion recovery (FLAIR), and CE MRI. Areas of CE were manually delineated. FET PET tumor volumes were segmented using a tumor-to-brain ratio ≥ 1.6. The percentage of overlapping volumes (OV), as well as Dice and Jaccard spatial similarity coefficients (DSC; JSC), were calculated. FLAIR images were evaluated visually. RESULTS: In 86% of patients (n = 43), the FET PET tumor volume was significantly larger than the volume of CE (21.5 ± 14.3 mL vs. 9.4 ± 11.3 mL; P < 0.001). Forty patients (80%) showed both an increased uptake of FET and CE. In these 40 patients, the spatial similarity between FET and CE was low (mean DSC, 0.39 ± 0.21; mean JSC, 0.26 ± 0.16). Ten patients (20%) showed no CE, and one of these patients showed no FET uptake. In 10% of patients (n = 5), increased FET uptake was present outside of areas of FLAIR hyperintensity. CONCLUSION: Our results show that the metabolically active tumor volume delineated by FET PET is significantly larger than tumor volume delineated by CE. The data strongly suggest that the information derived from FET PET should be integrated into the management of newly diagnosed glioblastoma patients. FUNDING: This work was supported by the Wilhelm-Sander Stiftung, Germany